Bridging social forestry and forest management units: Juxtaposing policy imaginaries with implementation practices in a case from Sulawesi - Tajuddin, Tajuddin; Supratman, Supratman; Salman, Darmawan; Yusran, Yusran (Forestry Faculty, Universitas Hasanuddin, 2019)
As the priority forestry development programs in Indonesia in recent years, Social Forestry policies (SF) and Forest Management Units (FMU or KPH) still indicate low performance. The SF program in particular, is dependent on the role of the KPH as an institution in realizing its expected goals. Using the theory of bureaucratic politics, this article presents the implementation of the SF program under the KPH system and how both programs can mutually support or inhibit the development of the other. The research was conducted using policy content analysis in the implementation of SF and KPH programs by applying interview methods, questionnaires and field observations that are presented both qualitatively and descriptively. We find that the development of SF cannot be separated from the role of the KPH bureaucracy due to the absence of bureaucratic institutions at the site level. SF sites are located in KPH working areas and perform a central role in all aspects of SF management. However, SF programs are not clearly stated as one of the main tasks and functions of KPHs and the existence of KPH interests in realizing independence without special budget allocations for the development of SF are obstacles to its implementation. KPH also still face regulatory issues that have not fully supported KPH operations resulting in weak institutions and independence to governing hierarchies due to the strong influence of the bureaucracy at the central and provincial levels. On the other hand, the SF program is still perceived as a rival of KPHs in forest management areas and further suffer from rigid regulations that are difficult to apply, making it challenging for SF to support the objectives of KPH programming. Under these conditions, KPH tend to limit SF schemes, thus privileging specific different forestry partnership schemes that are anticipated to support the independence of the KPH.